Wat Thammikārāmw̜ōrawihān Čhangwat Pračhūap Khīrī Khan - Somphong Suthinsak (Rōngphim Liangchīang, 1994)
History and description of Wat Thammikārāmw̨ōrawihān, Buddhist temple in Prachuap Khiri Khan Province and biographies of its lord abbots.